2009
DOI: 10.1007/s00403-009-0985-z
|View full text |Cite
|
Sign up to set email alerts
|

Rhodiola rosea ability to enrich cellular antioxidant defences of cultured human keratinocytes

Abstract: Keratinocytes are cells strongly exposed to oxidative stress, but normally good equipped for antioxidant responses. However, it has long been suggested that exogenous antioxidants could play a useful role in minimizing the adverse skin responses associated with such oxidant species. In this work it was paid attention to the extract of Rhodiola rosea L. roots by using the phytocomplex as a whole because of the important activity of its composition and mutual distribution of its components. We have measured the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
34
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 38 publications
2
34
0
Order By: Relevance
“…6 R. rosea exerts antioxidant effects and thereby reduced tissue injury, resulting from oxidative stress. 7,8 However, the efficacy of R. rosea in renal tissue damage after ureter obstruction has not been investigated. In the present study, we assessed the efficacy of R. rosea at alleviating the renal damage induced by unilateral ureter obstruction (UUO) in rats.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 R. rosea exerts antioxidant effects and thereby reduced tissue injury, resulting from oxidative stress. 7,8 However, the efficacy of R. rosea in renal tissue damage after ureter obstruction has not been investigated. In the present study, we assessed the efficacy of R. rosea at alleviating the renal damage induced by unilateral ureter obstruction (UUO) in rats.…”
Section: Introductionmentioning
confidence: 99%
“…A study carried out on keratinocytes revealed that R. rosea increased antioxidant enzyme levels, demonstrating reliable antioxidant activity. 7 Palumbo et al reported that R. rosea had antioxidant properties and acted as a neuroprotector of cortical neurons. 8 Our results also indicate that R. rosea possesses antioxidant activity.…”
mentioning
confidence: 99%
“…Rhodiola rosea has long been used as a medicinal plant and has been reported to have various pharmacological properties, including antifatigue and antistress activity [3], anticancer, antioxidant and immune enhancing and stimulating sexual activity [4], anti-inflammation [5], improvement of glucose and lipid metabolism [6, 7], antiarrhythmic effect [8], and enhancement of angiogenesis [9]. However, the effects of Rhodiola rosea on atherosclerotic lesions formation are still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Salidroside, a compound with the chemical structure of phenol glycosides, is an important kind of flavonoids extracted from the root of Rhodiola rosea [21], existed in seed coat of walnut and so on [22,23]. Besides roles in anti-inflammation [24], anti-oxidation [25], scavenging free radical [20], salidroside also can reduce ischemiamediated myocardial damage [26], moreover, it has been shown that salidroside has ability to inhibit the activity of tyrosinase which is the main rate-limiting enzyme in the process of melanin synthesis [20].…”
Section: Introductionmentioning
confidence: 99%